Comparison of flipped classroom and lecture-based models in a radiology residency training program - Weishu Hou; Yangyang Xue; Hongli Pan; Xuemei Zhao; Hongmin Shu; Xiaohu Li; Yongqiang Yu (BMC Medical Education)
Abstract Background The flipped classroom (FC) model is an effective teaching method that flips traditional teaching process dominated by teachers to students. Few studies have applied the FC model to the radiology residency training. Objective This study analyzed the learning ability, learning efficiency and satisfaction with teaching quality of an FC group of residents (n = 67) and compared the findings with those of a lecture-based (LB) teaching group (n = 60) at the Affiliated Hospital of Anhui Medical University. The aim was to evaluate the effectiveness of the FC model in the radiology residency training. Materials and methods The retrospective analysis involved students trained in the nervous system sub-group in the university’s radiology department between July 2018 and July 2023. The examination scores and subjective evaluations of learning ability and the different teaching models were collected and compared between the two groups. Results Practical examination scores were significantly higher in the FC group versus the LB group (83.7 ± 13.46 vs. 77.68 ± 5.53, P = 0.001). The theoretical score between the two groups did not differ appreciably (82.81 ± 11.31 vs. 80.25 ± 10.42, P = 0.320). Subjectively, more residents in FC group believed their learning ability was significant or negligibly improved compared to the LB group (both P < 0.05). The overall satisfaction with the FC teaching model was significantly higher than LB instruction (4.36 ± 0.94 vs. 3.88 ± 0.68, P = 0.008). Average scores of “good teaching”, “generic skills”, and “appropriate assessment” in the FC group were significantly higher than the scores in the LB group (4.36 ± 0.26 vs. 3.80 ± 0.44, P < 0.001; 4.45 ± 0.47 vs. 3.68 ± 0.65, P = 0.001; and 2.74 ± 0.44 vs. 3.98 ± 0.28, P < 0.001, respectively). Conclusion The FC teaching model is a feasible and effective approach for radiology residents to enhances their learning ability and efficiency, and improves their satisfaction with teaching quality.